Case Report: Pneumonia in a Patient With Combined Variable Immunodeficiency: COVID-19 or Pneumocystis Pneumonia? - Tehrani, Shabnam; Ziaie, Shadi; Kashefizadeh, Alireza; Fadaei, Mahta; Najafiarab, Hanieh; Keyvanfar, Amirreza (Frontiers in Medicine, 2022)
Combined variable immunodeficiency (CVID) is a primary immunodeficiency, characterized by impairment in immune system function. These patients are susceptible to opportunistic infections, which may mimic COVID-19 manifestations. Also, misdiagnosis or delayed diagnosis of opportunistic infections can lead to perilous consequences. We report a 28-year-old woman with a history of combined variable immunodeficiency disorder (CVID) and ulcerative colitis (UC) complained of fever, cough, and dyspnea. According to the clinical and radiological manifestations and the COVID-19 epidemic, she was admitted with a primary diagnosis of COVID-19 pneumonia. After a week, the patient did not respond to treatment, so she underwent bronchoscopy. Using polymerase chain reaction (PCR) methodology, we detected DNA of Pneumocystis jirovecii, the causative agent of a life-threatening pneumonia (PCP), in respiratory specimens. The patient was hypersensitive to common PCP treatments, so she was treated with high-dose clindamycin. However, the patient's clinical condition aggravated. Besides, we found evidence of pneumothorax, pneumomediastinum, and pneumopericardium in chest CT scan. We inserted a catheter for the patient to evacuate the air inside the mediastinum. Also, we added caspofungin to the treatment. The patient eventually recovered and was discharged from the hospital about a week later. Thus, during the COVID-19 epidemic, in febrile patients with respiratory symptoms, physicians should not think only of COVID-19. They must consider opportunistic infections such as PCP, especially in immunocompromised patients.